Maternal and neonatal outcomes in labor and at delivery when long QT syndrome is present. (2nd April 2016) - Tanaka, Hiroaki; Katsuragi, Shinji; Tanaka, Kayo; Sawada, Masami; Iwanaga, Naoko; Yoshimatsu, Jun; Ikeda, Tomoaki
Abstract: Objective : Women during labor may be susceptible to torsades de pointes (TdP), which may cause the fetal condition to deteriorate. The aim of the present investigation was to analyze maternal and fetal outcomes during labor when long QT syndrome (LQTS) was present. Methods : We examined the maternal and neonatal outcomes of 25 pregnancies (18 women) with LQT between 1995 and 2012 at the Department of Perinatology, National Cardiovascular Center, Japan. Maternal and neonatal outcomes including cardiovascular events, cardiovascular events within a week after delivery, caesarean delivery rate, still births, preterm births, and non-reassuring fetal heart rate pattern (NRFHR) during labor were investigated. Results : All the mothers survived, and no cardiovascular events occurred in labor or postpartum due to LQTS in either vaginal delivery or caesarean delivery. A total of 23 women (92%) had used beta blockers in this study. Caesarean delivery was performed due to NRFHR during labor in 5 pregnancies (20%). Conclusion : Delivery when LQTS is present has a low likelihood of cardiovascular events, but pregnancy with LQTS had a higher caesarean delivery rate due to NRFHR in labor. Most women used beta blockers in this study, and it is possible that beta blocker use prevents cardiovascular events during labor. NRFHR during labor may be related with inherited LQT through the mother.